2021
DOI: 10.2478/helm-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, immunological and genetic factors in the resistance and susceptibility to gastrointestinal nematodes of sheep in the peripartum period: A review

Abstract: Summary Parasitic diseases of sheep involving gastrointestinal nematodes (GIN) are one of the main problems that affect fl ock productivity, especially during the peripartum period. Around lambing, the ewes are immunosuppressed and the nematode faecal egg count (FEC) increases at four weeks before lambing, reaching a peak between the fourth and sixth week postpartum and subsequently decreasing towards weaning. Prolactin has been credited with a suppressive effect on immune system, along with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…The results reported a significant level of HMGB-1 in the dogs with nematode infections, attributable to their central immune response. An increase in HMGB-1 has been reported in different nematode infections in humans [ 44 ] and sheep [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results reported a significant level of HMGB-1 in the dogs with nematode infections, attributable to their central immune response. An increase in HMGB-1 has been reported in different nematode infections in humans [ 44 ] and sheep [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Starting on the 35th day of lactation (DL 35), the sheep were milked twice a day. Milk samples were collected from the morning and evening milking (at 05.00 a.m. and 07.00 p.m.) on days 35,42,49,56,63,70, and 77 of lactation (DL42, DL49, DL56, DL63, DL70, and DL77). In these days, the quantities of milk produced and the milk nutrient contents were measured.…”
Section: Experimental Protocol For Milk Evaluationmentioning
confidence: 99%
“…Figure5shows the average milk production (ml) on lactation days (DL)35,42,49,56, 63, 70, and 77 in the form of performance curves.Figure6represents the qualitative evaluation of milk relative to the percentage of protein, casein, lactose, and fat in the study groups.The percentage of protein, casein, lactose, and fat was significantly higher in the PG-treated group than in the control group. The albendazole-treated group, in turn, had a higher percentage of all components of the milk under test than the control group.…”
mentioning
confidence: 99%
“…Mourad et al (2001) reported that diarrhoea was the most important disease condition encountered in Djallonke sheep in Guinea, which often resulted in mortality of sheep, especially in lambs. Diarrhoea can be attributed to multiple causes ranging from nematode infestation (González-Garduño et al, 2021), to bacteria such as E. coli or poor nutritional management (Kusiluka et al, 1996). The prevalence in lambs is higher than in adult animals and causes higher rates of mortality in lambs compared to older animals in the flock (Mourad et al, 2001).…”
Section: Health Managementmentioning
confidence: 99%